Singing mice, songbirds, and more: models for FOXP2 function and dysfunction in human speech and language. - White, SA; Fisher, S; Geschwind, D; Scharff, C; Holy, T (2006)
In 2001, a point mutation in the forkhead box P2 (FOXP2) coding sequence was identified as the basis of an inherited speech and language disorder suffered by members of the family known as "KE." This mini-symposium review focuses on recent findings and research-in-progress, primarily from five laboratories. Each aims at capitalizing on the FOXP2 discovery to build a neurobiological bridge between molecule and phenotype. Below, we describe genetic through behavioral techniques used currently to investigate FoxP2 in birds, rodents, and humans for discovery of the neural bases of vocal learning and language.